BUDAYA KERJA DAN IKLIM ORGANISASI PENGARUHNYA TERHADAP KOMITMEN ORGANISASI DI PUSKESMAS SUNGAI PIRING KABUPATEN INDRAGIRI HILIR - jurnalmap map; NurÔÇÖafni ÔÇÄ; Hadi Susanto; Esa Wahyu Endarti (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study aims to determine the effect of work culture and organizational climate on organizational commitment in the Sungai Piring Community Health Center, Indragiri Hilir Regency. The study population included all employees of Sungai Piring Puskesmas, Indragiri Hilir Regency, totaling 76 people, with an analysis unit in the form of employees. Data collection is done by questionnaire. Then the data were analyzed using multiple regression analysis techniques.The results showed that work culture and organizational climate partially had a significant effect on organizational commitment. Work culture is the dominant variable influencing organizational commitment in the Sungai Piring Community Health Center in Indragiri Hilir Regency. Simultaneously, work culture and organizational climate significantly influence organizational commitment. Organizational goals will be easily achieved if the organization can develop a work culture and create a healthy organizational climate and encourage organizational commitment as happy to spend the rest of his career with the organization.